Predictors of delirium in patients with acute decompensated heart failure at a cardiac intensive care unit. (3rd May 2023) - Carvalho, M; Cabral, M; Goncalves, C; Vazao, A; Fernandes, S; Graca Santos, L; Morais, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Delirium is commonly observed in critically ill patients and is associated with a worse overall prognosis in patients hospitalized with acute decompensated heart failure. However, in patients with acute decompensated heart failure (ADHF), the impact of delirium on prognosis and the factors that influence it have not been thoroughly examined. Objective: To study the predictors of delirium in patients hospitalized in the cardiac intensive care unit (CICU) due to acute decompensated heart failure. Methods: We retrospectively analyzed 105 patients admitted to a CICU due to ADHF. Delirium was diagnosed based on the Confusion Assessment Method for ICU (CAM-ICU) during CICU stay. Echocardiography and laboratory measurements were performed during hospitalization. A logistic regression analysis was performed, looking for independent predictors of delirium development. Results: Delirium was observed in 25 patients (23.8%) during CICU hospitalization. Multivariable analysis revealed that older age (odds ratio [OR]: 7.6; 95% confidence interval [CI]: 3.2-21.2; p<0.001), previous diagnosis of dementia (OR: 7.31, 95% CI: 3.65-14.91, p<0.001), high plasma level of C reactive protein > 79 mg/L (OR: 1.26, 95% CI: 1.09-1.61, p=0.031), and prior alcohol misuse (OR: 5.4; 95% CI: 2.76-13.40; p=0.003) as significant independent determinants of delirium. Furthermore, we determined that delirium was an independent predictor of in-hospital mortality (OR: 1.93, 95% CI 1.1-3.4.1, p=0.033). There was no relationship to the previous medical history of arterial hypertension, diabetes mellitus, or left ventricular ejection fraction. Conclusions: In patients with ADHF, the development of delirium during CICU stay is associated with a higher risk of in-hospital mortality. Older age, dementia, high levels of C reactive protein, and alcohol misuse were identified as predictors of delirium. Therefore, this clinical entity's early diagnosis and proper management are essential.